1995
DOI: 10.1177/00220345950740111201
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Levels of Suspected Periodontal Pathogens in Relation to Periodontal Status and Treatment

Abstract: The primary ecological niche for suspected periodontal pathogens seems to be the subgingival area, even though periodontal pathogens are also frequently recovered from saliva. The interrelationship of different periodontal conditions and the salivary levels of suspected periodontal pathogens is not known. In the present study, salivary levels of Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Campylobacter rectus, and Peptostreptococcus micros were determined by bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 29 publications
1
64
0
1
Order By: Relevance
“…In the present study, where the detection of selected pathogens was examined in a large, true population-based study population, this seemed to be the case for P. gingivalis, P. intermedia, T. denticola, and A. actinomycetemcomitans but, surprisingly, not for T. forsythensis. In pathogen carriers, the proportion of pathogens increases in saliva due to deteriorating periodontal status (34), indicating that a subject with advanced periodontitis can serve as a potential source of pathogens to his/her close contacts. Monitoring the carriage pattern of periodontal pathogens at the general population level may help in designing preventive strategies to attempt to control the acquisition of less beneficial members of the human oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, where the detection of selected pathogens was examined in a large, true population-based study population, this seemed to be the case for P. gingivalis, P. intermedia, T. denticola, and A. actinomycetemcomitans but, surprisingly, not for T. forsythensis. In pathogen carriers, the proportion of pathogens increases in saliva due to deteriorating periodontal status (34), indicating that a subject with advanced periodontitis can serve as a potential source of pathogens to his/her close contacts. Monitoring the carriage pattern of periodontal pathogens at the general population level may help in designing preventive strategies to attempt to control the acquisition of less beneficial members of the human oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown C. rectus to be associated with higher levels of clinical attachment loss, bleeding on probing of the sampled site, and probing depth (121,(130)(131)(132)(133). Furthermore, the abundance of C. rectus has been reported to be elevated significantly in patients with chronic gingivitis and moderate periodontitis but not in severe periodontitis patients, suggesting that this organism is associated with the early stages of periodontitis (130,134).…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Other studies have shown that many of these species are also recovered from saliva [1,10,35]. For instance, von Troil-Linden et al [35], using bacterial culture, demonstrated different levels of A. actinomycetemicomitans, P. gingivalis, C. rectus, and P. micros in saliva of subjects with varying degrees of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that many of these species are also recovered from saliva [1,10,35]. For instance, von Troil-Linden et al [35], using bacterial culture, demonstrated different levels of A. actinomycetemicomitans, P. gingivalis, C. rectus, and P. micros in saliva of subjects with varying degrees of periodontitis. It has been estimated that Leptotrichia spp., nonpigmented Prevotella spp., P. intermedia, Capnocytophaga spp., Bacteriodes gracilis, and Prevotella loescheii are present in the saliva of 55% to 76% of young women [21].…”
Section: Introductionmentioning
confidence: 99%